Assessing the Validity of the Cox, Zmud, and Clark Material-Requirements-Planning Audit Instrument - Kinicki, Angelo J.; Heyl, Jeff; Callarman, Thomas E. (Academy of Management Journal, 1986)
In this article the authors discuss two studies that examined the effectiveness of material requirements planning (MRP) systems. They note that one study found that MRP users found improvements in inventory turnover, lead times of deliveries and a variety of other benefits. Another study found that the implementation of a MRP was met with lack of support from top management and that users found the system complicated. The authors note that the system was found to be designed improperly; however, the authors of that study did not provide any evidence to be reviewed. In their research the authors aim to examine the content validity of that study based on organizational and technical validity constructs.